Prove using induction that n3−n is divisible by 6 whenever n>0
My attempt:
Base step: For n=1
13−1=0.
0 which is divisible by 6.
Thus, n=1 is true.
Assumption step: Let n=k
k3−k
Inductive step: f(k+1)−f(k)
(k+1)3−(k+1)−k3−k
This is where I am stuck. How do I go forward to prove using induction that n3−n is divisible by 6?
Answer
In your assumption step, you need to assume the statement is true for n=k, i.e. k3−k is divisible by 6.
In the induction step, expand and simplify (k+1)3−(k+1):
(k+1)3−(k+1)=k3+3k2+3k+1−k−1=k3−k+3k2+3k=(k3−k)+3k2+3k=(k3−k)+3k(k+1)
Note that k3−k is divisible by 6 by the inductive hypothesis (the assumption). k and k+1 are consecutive integers, so their product must be even. Hence 3k(k+1) is also divisible by 6. Thus, whenever k3−k is divisible by 6, we also have that (k+1)3−(k+1) is divisible by 6.
No comments:
Post a Comment